Ultraviolet Response in Coplanar Silicon Avalanche Photodiodes with CMOS Compatibility - Qiaoli Liu; Li Xu; Yuxin Jin; Shifeng Zhang; Yitong Wang; Anqi Hu; Xia Guo (Sensors, 2022)
Highly sensitive ultraviolet (UV) photodetectors are highly desired for industrial and scientific applications. However, the responsivity of silicon photodiodes in the UV wavelength band is relatively low due to high-density Si/SiO2 interface states. In this paper, a coplanar avalanche photodiode (APD) was developed with a virtual guard ring design. When working in Geiger mode, it exhibited a strong UV response. The responsivity of 4 × 103 A/W (corresponding to a gain of 8 × 106) at 261 nm is measured under the incident power of 0.6 μW with an excess bias of 1.5 V. To the best of our knowledge, the maximum 3-dB bandwidth of 1.4 GHz is the first report ever for a Si APD when working in the Geiger mode in spite of the absence of an integrated CMOS read-out circuit.